Safety and efficacy of l‐valine produced by fermentation using Corynebacterium glutamicum KCCM 11201P for all animal species. (31st January 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: The product subject of this assessment is l ‐valine produced by fermentation using a non‐genetically modified strain of Corynebacterium glutamicum (KCCM 11201P). It is intended to be used in feed and water for drinking for all animal species and categories. Species identity of the production organism was confirmed and the strain was sensitive to antibiotics at concentrations below thresholds specified by EFSA, thus C . glutamicum KCCM 11201P may be considered safe by the qualified presumption of safety (QPS) approach. No viable cells of C . glutamicum were detected in the final product. The amount of identified material exceeded 98.6% on 'as is' basis, and no impurities of concern were detected. The use of l ‐valine produced by C . glutamicum KCCM 11201P is safe for target species when supplemented to diets in appropriate amounts, for the consumer and the environment. The product l ‐valine produced by C . glutamicum (KCCM 11201P) is considered not to be an irritant or a dermal sensitiser, and does not cause acute inhalation toxicity. The additive is an effective source of valine for all species. For the supplemental l ‐valine to be as efficacious in ruminants as in non‐ruminant species, it requires protection against microbial degradation in the rumen.